Tunisian date (Phoenix dactylifera L.) by-products: Characterization and potential effects on sensory, textural and antioxidant properties of dairy desserts. (1st December 2015) - Jridi, Mourad; Souissi, Nabil; Salem, Marwa Ben; Ayadi, M.A.; Nasri, Moncef; Azabou, Samia
Highlights: Date syrups and powders were incorporated in dairy desserts as sweetening agents. Syrup polysaccharides contribute to better maintain dairy dessert texture. Date by-products enhanced apparent viscosity and reduced syneresis. Natural antioxidant agents in date by-products lead to improve functionality. Abstract: Three Tunisian date varieties, Deglet Nour, Kentichi and Allig, served to produce syrups and powders, which were then examined for their physico-chemical composition and antioxidant properties. Different proportions of these sweetening-like agents were incorporated to produce nine different formulations of dairy desserts, with lower amount of added sugars to avoid any artificial flavoring or coloring agents. Sensory and color evaluation data revealed that incorporating Deglet Nour and Kentichi syrup offers the most desirable formulation. Furthermore, syrup polysaccharides and fibers contribute to better maintain the final product texture. In addition, date by-products create a good source of natural thickening agents, involved in enhancing apparent viscosity and spontaneous exudation. Thanks to their high content in phenolic compounds, date by-products considerably improve antioxidant activities of the formulated desserts. Therefore, they could be valued as natural ingredients in the formulation of novel dairy products with high nutritional-properties.